High-strength aluminum alloy power cable

By introducing modified attapulgite, nano-hydrotalcite and coated potassium titanate whiskers into the outer sheath of aluminum alloy power cable, the cracking problem and insufficient heat dissipation of the cable during bending operation are solved, and the comprehensive performance improvement of high strength and good heat dissipation is achieved.

CN120757902APending Publication Date: 2025-10-10HEBEI SONGQIAO CROSS LINKED CABLE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511092184.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-05
Publication Date
2025-10-10

AI Technical Summary

Technical Problem

Existing high-strength aluminum alloy power cables are prone to cracking and breaking during bending operations, and their heat dissipation performance is insufficient, causing the cable temperature to rise, affecting their service life and current carrying capacity.

Method used

Modified attapulgite, nano-hydrotalcite and coated potassium titanate whiskers are used as fillers to form a reinforced skeleton and thermal conductive path in the outer sheath to improve flexibility and heat dissipation performance.

Benefits of technology

It improves the tensile strength and crack resistance of the cable, while significantly improving the heat dissipation performance and improving the thermal stability and service life of the cable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of cables, and provides a high-strength aluminum alloy power cable. The cable is sequentially provided with an aluminum alloy conductor layer and an outer sheath layer from inside to outside. The outer sheath layer is prepared from the following raw materials in parts by weight: 40 to 50 parts of low-density polyethylene, 20 to 30 parts of ethylene propylene diene monomer, 8 to 15 parts of maleic anhydride grafted ethylene-vinyl acetate copolymer, 20 to 25 parts of modified attapulgite, 10 to 15 parts of nano hydrotalcite, 6 to 8 parts of coated potassium titanate whisker, 1.5 to 2 parts of dicumyl peroxide, 10 to 15 parts of magnesium hydroxide, 3 to 5 parts of zinc borate and 0.3 to 0.5 part of antioxidant 1010. 0.2-0.4 part of dilauryl thiodipropionate, 4-5 parts of a calcium-zinc composite stabilizer and 0.5-1 part of calcium stearate. According to the invention, the flexibility of the cable outer sheath is improved while high strength is ensured, and the heat dissipation performance of the high-strength outer sheath is improved at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of cables, and in particular to a high-strength aluminum alloy power cable. Background Art

[0002] As a critical infrastructure for power transmission and distribution, the performance and quality of power cables are directly related to the safe, stable, and efficient operation of power systems. Traditional copper power cables are widely used due to their excellent electrical conductivity. However, copper resources are relatively scarce and expensive, resulting in high costs for copper cables, which limits their application in some large-scale power projects. In contrast, aluminum alloy cables, with their advantages of light weight, low cost, and corrosion resistance, are gradually becoming a powerful alternative to copper cables. High-strength aluminum alloy power cables, with their higher mechanical strength and better overall performance, show great potential for application in long-distance power transmission, large-span overhead lines, and power transmission in special environments.

[0003] In order to achieve high strength, existing outer sheath materials often need to add a large amount of reinforcing fillers or adopt a high-hardness polymer matrix, but this will lead to a decrease in the flexibility of the material. During the cable laying process, especially when bending operations are required, the outer sheath with insufficient flexibility is prone to cracking, breaking and other problems, affecting the normal installation and use of the cable. For example, in some mobile cable application scenarios that require frequent bending, this contradiction is particularly obvious. The power cable will generate heat during operation. If the heat dissipation structure of the outer sheath is not designed reasonably, the heat cannot be dissipated in time, which will cause the cable temperature to rise, accelerate the aging of the insulation material, and reduce the current carrying capacity and service life of the cable. Most of the existing high-strength outer sheaths focus on mechanical properties and protective performance, and pay relatively little attention to heat dissipation performance. There is a lack of effective heat dissipation channels or heat dissipation structures, which affects the overall performance of the cable. In order to solve the above technical problems, the present invention proposes a new high-strength aluminum alloy power cable. Summary of the Invention

[0004] The present invention proposes a high-strength aluminum alloy power cable, which improves the flexibility of the cable outer sheath while ensuring high strength, and improves the situation where cracking and breakage easily occur during bending operations due to insufficient flexibility; at the same time, the heat dissipation performance of the high-strength outer sheath is improved, and the problem of increased cable temperature and accelerated aging of insulation materials due to unreasonable heat dissipation design is improved.

[0005] The technical solutions of the present invention are as follows: In a first aspect, the present invention provides a high-strength aluminum alloy power cable, which is provided with an aluminum alloy conductor layer and an outer sheath layer in sequence from the inside to the outside, wherein the outer sheath layer comprises the following raw materials in parts by weight: 40-50 parts of low-density polyethylene, 20-30 parts of EPDM rubber, 8-15 parts of maleic anhydride grafted ethylene-vinyl acetate copolymer, 20-25 parts of modified attapulgite, 10-15 parts of nano-hydrotalcite, 6-8 parts of coated potassium titanate whiskers, 1.5-2 parts of dicumyl peroxide, 10-15 parts of magnesium hydroxide, 3-5 parts of zinc borate, 0.3-0.5 parts of antioxidant 1010, 0.2-0.4 parts of dilauryl thiodipropionate, 4-5 parts of calcium-zinc composite stabilizer, and 0.5-1 part of calcium stearate.

[0006] Maleic anhydride-grafted ethylene-vinyl acetate copolymer plays a key role as a compatibilizer in cable outer sheaths. The anhydride groups in its molecular structure react chemically with reactive groups on the filler surface, forming chemical bonds and improving the filler's dispersion within the matrix. Furthermore, the compatibilizer reduces interfacial tension between the filler and the matrix, enhancing interfacial bonding and enabling more efficient stress transfer between the filler and the matrix. This compatibilization not only improves the mechanical properties of the cable outer sheath but also enhances its low-temperature toughness, making the cable less susceptible to cracking and breakage during bending.

[0007] After alkaline pretreatment and surface modification with a silane coupling agent (KH550), the modified attapulgite significantly increases its surface activity and strengthens its bonding with the substrate. Within the cable outer sheath, the modified attapulgite forms a reinforcing framework, providing additional mechanical support for the substrate and thereby increasing the cable's tensile strength and elongation. Furthermore, the modified attapulgite's layered structure helps create a thermal conductivity pathway, improving the cable's thermal conductivity. This dual function of reinforcing the framework and providing a thermal pathway ensures that the cable maintains high strength while also exhibiting excellent heat dissipation.

[0008] As a further technical solution, the preparation method of the modified attapulgite includes: immersing the attapulgite pretreated with alkali solution in a KH550 ethanol solution with a mass concentration of 4%-6%, a solid-liquid weight ratio of 1:9-1:11, ultrasonic treatment at 70±5°C and a power of 800-1000 W for 0.8-1.2 h, centrifugal separation at 3000-4000 rpm for 10-15 min, and vacuum drying at 80±5°C to a moisture content of ≤0.3%.

[0009] As a further technical solution, the alkali solution pretreatment step includes: adding attapulgite to a 0.4-0.6 mol / L NaOH aqueous solution at a temperature of 55-65°C, with a solid-liquid weight ratio of 1:15-1:20, stirring at 200-300 rpm for 1.5-2.5 hours, centrifuging, and washing with deionized water until the filtrate has a pH of 7.0±0.5.

[0010] As a further technical solution, the preparation method of the coated potassium titanate whiskers includes: immersing the potassium titanate whiskers in a KH570 solution, stirring at 45-55°C and 100-150 rpm for 30-50 min, and drying with hot air at 80±5°C to a moisture content of ≤1.0%; placing the pretreated whiskers in a fluidized bed, spraying nano-SiO2 sol, and heat treating at 120±5°C for 0.5-1 h after coating to obtain the whiskers.

[0011] As a further technical solution, the potassium titanate whiskers have a diameter of 0.2-0.5 μm and a length of 20-50 μm.

[0012] As a further technical solution, the weight ratio of KH570, water and ethanol in the KH570 solution is 2.5-3.5:75-85:5-15, and the weight ratio of potassium titanate whiskers to KH570 solution is 1:12-1:15.

[0013] As a further technical solution, the ratio of the sprayed nano-SiO2 sol to the pretreated whiskers is 0.3-0.5 mL / g.

[0014] As a further technical solution, the conditions for spraying the nano-SiO2 sol are as follows: an inlet air temperature of 110-120°C, an atomization pressure of 0.15-0.25 MPa, and a spraying rate of 8-12 mL / min.

[0015] In a second aspect, the present invention provides a method for preparing a high-strength aluminum alloy power cable, comprising the following steps: Mix low-density polyethylene and EPDM rubber at a temperature of 155-165°C and a rotation speed of 40-50 rpm for 3-5 minutes; add maleic anhydride grafted ethylene-vinyl acetate copolymer, heat to 170-180°C, mix at 70-80 rpm for 5-6 minutes; add modified attapulgite and hydrotalcite in sequence, stir at 165-170°C and 50-60 rpm for 6-8 minutes. min, finally, potassium titanate whiskers, magnesium hydroxide, zinc borate, antioxidant 1010, dilauryl thiodipropionate, calcium zinc composite stabilizer, and calcium stearate are added and stirred at 140-150° C. and 30-40 rpm for 10-15 min; dicumyl peroxide is added, the speed is increased to 100-120 rpm, and vulcanization is carried out at 170-180° C. for 6-8 min. The cable is extruded and coated on the outside of the aluminum alloy conductor layer through a single-screw extruder, the temperature of the first zone of the extruder is 160-165° C., the temperature of the second zone is 165-170° C., the temperature of the third zone is 175-180° C., and the temperature of the die head is 180-185° C. After air cooling and irradiation cross-linking, the high-strength aluminum alloy power cable is obtained.

[0016] As a further technical solution, the energy of the irradiated cross-linking electrons is 1.5-2 MeV, and the irradiation dose is 15-20 kGy.

[0017] The working principle and beneficial effects of the present invention are: The present invention introduces three fillers: modified attapulgite, nano-hydrotalcite, and coated potassium titanate whiskers, and utilizes the synergistic effect between them to significantly improve the heat dissipation capacity of the cable outer sheath. Modified attapulgite has a unique layered structure and a large specific surface area, which can form an effective heat conduction path; nano-hydrotalcite forms a barrier effect in the matrix with its lamellar structure and participates in the construction of the heat conduction network; coated potassium titanate whiskers reduce the interfacial thermal resistance through surface modification, improve the stress transfer efficiency, and further enhance the thermal conductivity. These three fillers complement each other in the matrix and jointly construct an efficient three-dimensional heat conduction network, thereby significantly improving the heat dissipation capacity of the cable outer sheath.

[0018] The potassium titanate whiskers coated in the present invention reduce their surface energy through surface modification, thereby reducing the interfacial thermal resistance with the substrate. This surface modification also enhances the interfacial bonding between the whiskers and the substrate, allowing for more efficient stress transfer between the whiskers and the substrate. In cable outer sheaths, the potassium titanate whiskers act as thermal conductivity enhancers, significantly improving the cable's thermal conductivity. Furthermore, their high aspect ratio and excellent mechanical properties provide additional reinforcement to the substrate, increasing the cable's tensile strength and crack resistance.

[0019] The nano-hydrotalcite in this invention, with its unique lamellar structure, plays a dual role in the cable outer sheath. First, its lamellar structure creates a barrier effect within the matrix, effectively inhibiting the diffusion of thermal decomposition products, thereby improving the cable's thermal stability. Second, the nano-hydrotalcite participates in the construction of a thermally conductive network, enhancing the cable's heat dissipation capacity through its high thermal conductivity. This dual effect of lamellar barrier and thermal conductivity makes nano-hydrotalcite a key factor in improving the thermal stability and heat dissipation performance of cable outer sheaths. DETAILED DESCRIPTION

[0020] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts are within the scope of protection of the present invention.

[0021] It should be noted that the low-density polyethylene of the present invention was purchased from PetroChina Jilin Petrochemical Company with the brand name DFDA-7042; EPDM rubber was purchased from Dow Chemical (China) Co., Ltd. with the brand name EPDM725P; maleic anhydride grafted ethylene-vinyl acetate copolymer was purchased from Nanjing Sutai Polymer Technology Co., Ltd. The preparation method of the SiO2 sol in the present invention is as follows: 380 mL of ethanol, 40 mL of water and 4 mL of ammonia water with a mass concentration of 25% are mechanically stirred at 30°C and 300 rpm to obtain a mixed solution, 10 mL of ethyl orthosilicate and 100 mL of ethanol are mixed and added to the mixed solution, stirring is continued at 30°C and 400 rpm for 30 minutes, and then the reaction is continued for 6 hours. Stirring is stopped, and the mixture is allowed to stand for 6 hours. The supernatant is discarded at 12,000 rpm, and the precipitate is washed with ethanol 3 times and water 2 times. The washed precipitate is added with 100 mL of deionized water and ultrasonically dispersed at 200 W for 10 minutes to obtain a stable SiO2 sol.

[0022] Example 1 The present embodiment provides a high-strength aluminum alloy power cable, which includes an aluminum alloy conductor layer and an outer sheath layer, which are sequentially provided from the inside to the outside. The outer sheath layer comprises the following raw materials in parts by weight: 45 parts of low-density polyethylene, 25 parts of ethylene propylene diene monomer rubber, 10 parts of maleic anhydride grafted ethylene-vinyl acetate copolymer, 22 parts of modified attapulgite, 12 parts of nano-hydrotalcite, 7 parts of coated potassium titanate whiskers, 1.8 parts of dicumyl peroxide, 12 parts of magnesium hydroxide, 4 parts of zinc borate, 0.4 parts of antioxidant 1010, 0.3 parts of dilauryl thiodipropionate, 4.5 parts of calcium-zinc composite stabilizer, and 0.8 parts of calcium stearate. Among them, the preparation method of modified attapulgite includes: adding 0.5 mol / L NaOH aqueous solution at 60°C with a solid-liquid weight ratio of 1:18 to the attapulgite, stirring at 250 rpm for 2 hours, centrifuging, washing with deionized water until the pH of the filtrate is 7.0 to obtain the attapulgite pretreated with alkali solution, immersing the attapulgite pretreated with alkali solution in a 5% KH550 ethanol solution with a solid-liquid weight ratio of 1:10, ultrasonically treating at 70°C and 900 W power for 2 hours, centrifuging at 3500 rpm for 12 minutes, and vacuum drying at 80°C to a moisture content of 0.3%.

[0023] The preparation method of coated potassium titanate whiskers includes: immersing potassium titanate whiskers with an average diameter of 0.3 μm and an average length of 40 μm in a KH570 solution, wherein the weight ratio of KH570, water and ethanol in the KH570 solution is 3:70:10, and the weight ratio of potassium titanate whiskers to the KH570 solution is 1:13; stirring at 50°C and 12 rpm for 40 minutes, and hot air drying at 80°C to a moisture content of 1.0%; placing the pretreated whiskers in a fluidized bed, spraying nano-SiO2 sol, wherein the amount ratio of nano-SiO2 sol to the pretreated whiskers is 0.4 mL / g, controlling the inlet temperature at 115°C, the atomization pressure at 0.2 MPa, and the spraying rate at 10 mL / min, and heat treating at 120°C for 0.7 h after coating to obtain the whiskers.

[0024] A method for preparing a high-strength aluminum alloy power cable comprises the following steps: Low-density polyethylene and EPDM rubber were mixed at a temperature of 160°C and a rotation speed of 45 rpm for 4 minutes; maleic anhydride grafted ethylene-vinyl acetate copolymer was added, the temperature was raised to 175°C, and the mixing was carried out at 75 rpm for 5 minutes; modified attapulgite and hydrotalcite were added in sequence and stirred at 168°C and 55 rpm for 7 minutes; finally, potassium titanate whiskers and magnesium hydroxide, zinc borate, antioxidant 1010, dilauryl thiodipropionate, calcium zinc composite stabilizer, calcium stearate were added at 14 5℃, 35rpm stirring for 12min; adding dicumyl peroxide, increasing the speed to 110rpm, vulcanizing at 175℃ for 7min, and extruding and coating on the outside of the aluminum alloy conductor layer through a single-screw extruder. The temperature of the first zone of the extruder is 162℃, the temperature of the second zone is 167℃, the temperature of the third zone is 178℃, the temperature of the head is 182℃, and the high-strength aluminum alloy power cable is obtained after air cooling and cross-linking at an electron energy of 1.8Mev and an irradiation dose of 18kGy.

[0025] Example 2 The present embodiment provides a high-strength aluminum alloy power cable, which includes an aluminum alloy conductor layer and an outer sheath layer, which are sequentially provided from the inside to the outside. The outer sheath layer comprises the following raw materials in parts by weight: 40 parts of low-density polyethylene, 20 parts of ethylene propylene diene monomer rubber, 8 parts of maleic anhydride grafted ethylene-vinyl acetate copolymer, 20 parts of modified attapulgite, 10 parts of nano-hydrotalcite, 6 parts of coated potassium titanate whiskers, 1.5 parts of dicumyl peroxide, 10 parts of magnesium hydroxide, 3 parts of zinc borate, 0.3 parts of antioxidant 1010, 0.2 parts of dilauryl thiodipropionate, 4 parts of calcium-zinc composite stabilizer, and 0.5 parts of calcium stearate. Among them, the preparation method of modified attapulgite includes: adding 0.4 mol / L NaOH aqueous solution at 55°C with a solid-liquid weight ratio of 1:15 to the attapulgite, stirring at 200 rpm for 1.5 hours, centrifuging, washing with deionized water until the pH of the filtrate is 7.0 to obtain the attapulgite pretreated with alkali solution, immersing the attapulgite pretreated with alkali solution in a 4% KH550 ethanol solution with a solid-liquid weight ratio of 1:9, ultrasonically treating at 70°C and 800W power for 0.8 hours, centrifuging at 3000 rpm for 10 minutes, and vacuum drying at 80°C to a moisture content of 0.3%.

[0026] The preparation method of coated potassium titanate whiskers includes: immersing potassium titanate whiskers with an average diameter of 0.3 μm and an average length of 40 μm in a KH570 solution, wherein the weight ratio of KH570, water and ethanol in the KH570 solution is 2.5:75:5, and the weight ratio of potassium titanate whiskers to the KH570 solution is 1:12; stirring at 45°C and 100 rpm for 30 minutes, and drying with hot air at 80°C to a moisture content of 1.0%; placing the pretreated whiskers in a fluidized bed, spraying nano-SiO2 sol, wherein the amount ratio of nano-SiO2 sol to the pretreated whiskers is 0.3 mL / g, controlling the inlet temperature at 110°C, the atomization pressure at 0.15 MPa, and the spraying rate at 8 mL / min, and heat treating at 120°C for 0.5 h after coating to obtain the whiskers.

[0027] A method for preparing a high-strength aluminum alloy power cable comprises the following steps: Low-density polyethylene and EPDM rubber were mixed at a temperature of 155°C and a rotation speed of 40 rpm for 3 minutes; maleic anhydride grafted ethylene-vinyl acetate copolymer was added, the temperature was raised to 170°C and the mixing speed was 70 rpm for 5 minutes; modified attapulgite and hydrotalcite were added in sequence and stirred at 165°C and 50 rpm for 6 minutes. min, and finally, potassium titanate whiskers, magnesium hydroxide, zinc borate, antioxidant 1010, dilauryl thiodipropionate, calcium zinc composite stabilizer, and calcium stearate are added and stirred at 140°C and 30 rpm for 10 min; dicumyl peroxide is added, the speed is increased to 100 rpm, and vulcanization is carried out at 170°C for 6 min. The cable is extruded and coated on the outside of the aluminum alloy conductor layer through a single-screw extruder, the temperature of the first zone of the extruder is 160°C, the temperature of the second zone is 165°C, the temperature of the third zone is 175°C, and the temperature of the die head is 180°C. The cable is air-cooled and shaped, and then irradiated and cross-linked at an electron energy of 1.5 MeV and an irradiation dose of 15 kGy to obtain a high-strength aluminum alloy power cable.

[0028] Example 3 The present embodiment provides a high-strength aluminum alloy power cable, which includes an aluminum alloy conductor layer and an outer sheath layer, which are sequentially provided from the inside to the outside. The outer sheath layer comprises the following raw materials in parts by weight: 50 parts of low-density polyethylene, 30 parts of EPDM rubber, 15 parts of maleic anhydride grafted ethylene-vinyl acetate copolymer, 25 parts of modified attapulgite, 15 parts of nano-hydrotalcite, 8 parts of coated potassium titanate whiskers, 2 parts of dicumyl peroxide, 15 parts of magnesium hydroxide, 5 parts of zinc borate, 0.5 parts of antioxidant 1010, 0.4 parts of dilauryl thiodipropionate, 5 parts of calcium-zinc composite stabilizer, and 1 part of calcium stearate. Among them, the preparation method of modified attapulgite includes: adding 0.6 mol / L NaOH aqueous solution at 65°C with a solid-liquid weight ratio of 1:20 to the attapulgite, stirring at 300 rpm for 2.5 hours, centrifuging, washing with deionized water until the pH of the filtrate is 7.0 to obtain the attapulgite pretreated with alkali solution, immersing the attapulgite pretreated with alkali solution in a 6% KH550 ethanol solution with a solid-liquid weight ratio of 1:11, ultrasonically treating at 70°C and a power of 1000 W for 1.2 hours, centrifuging at 4000 rpm for 15 minutes, and vacuum drying at 80°C to a moisture content of 0.3%.

[0029] The preparation method of the coated potassium titanate whisker comprises the following steps: immersing potassium titanate whiskers with an average diameter of 0.3 μm and an average length of 40 μm in a KH570 solution, wherein the weight ratio of KH570, water and ethanol in the KH570 solution is 3.5:85:15, the weight ratio of the potassium titanate whisker and the KH570 solution is 1:15, stirring at 55 DEG C and 150 rpm for 50 min, and drying at 80 DEG C until the water content is 1.0%; placing the pretreated whisker in a fluidized bed, spraying nano-SiO2 sol, the amount ratio of which to the pretreated whisker is 0.5 mL / g, controlling the air inlet temperature to be 120 DEG C, the atomization pressure to be 0.25 MPa, and the spraying speed to be 12 mL / min, and performing heat treatment at 120 DEG C for 1 h after coating to obtain the coated potassium titanate whisker.

[0030] The preparation method of the high-strength aluminum alloy power cable comprises the following steps: The low-density polyethylene and the ethylene-propylene-diene rubber are mixed at a temperature of 165 DEG C and a rotating speed of 50 rpm for 5 min; the maleic anhydride grafted ethylene-vinyl acetate copolymer is added, the temperature is increased to 180 DEG C, and the rotating speed is increased to 80 rpm for mixing for 6 min; the modified attapulgite and the hydrotalcite are added in sequence, and stirring is performed at 170 DEG C and 60 rpm for 8 min; finally, the potassium titanate whisker, the magnesium hydroxide, the zinc borate, the antioxidant 1010, the dilauryl thiodipropionate, the calcium-zinc composite stabilizer and the calcium stearate are added, and stirring is performed at 150 DEG C and 40 rpm for 15 min; the dicumyl peroxide is added, the rotating speed is increased to 120 rpm, and vulcanization is performed at 180 DEG C for 8 min; the coated aluminum alloy conductor layer is extruded by using a single-screw extruder, the temperature of the first zone of the extruder is 165 DEG C, the temperature of the second zone is 170 DEG C, the temperature of the third zone is 180 DEG C, and the temperature of the die head is 185 DEG C; air cooling and shaping are performed; and the high-strength aluminum alloy power cable is obtained after irradiation crosslinking under the conditions that the electronic energy is 2Mev and the irradiation dosage is 20 kGy.

[0031] Comparative Example 1 The adjustment is made on the basis of Example 1, and the difference from Example 1 is that the maleic anhydride grafted ethylene-vinyl acetate copolymer is not contained in the raw materials.

[0032] Comparative Example 2 The adjustment is made on the basis of Example 1, and the difference from Example 1 is that the modified attapulgite is replaced by the same amount of attapulgite which is not modified.

[0033] Comparative Example 3 The adjustment is made on the basis of Example 1, and the difference from Example 1 is that the modified attapulgite is not contained in the raw materials.

[0034] Comparative Example 4 The adjustment is made on the basis of Example 1, and the difference from Example 1 is that the coated potassium titanate whisker is replaced by the same amount of potassium titanate whisker.

[0035] Comparative Example 5 Adjustments were made based on Example 1, except that the raw materials did not contain coated potassium titanate whiskers.

[0036] Comparative Example 6 Adjustments were made based on Example 1, except that the raw materials did not contain nano-hydrotalcite.

[0037] Comparative Example 7 Adjustments were made based on Example 1, except that the EPDM rubber was replaced with low-density polyethylene.

[0038] Comparative Example 8 Adjustments were made based on Example 1, except that the raw materials did not contain modified attapulgite, nano-hydrotalcite, and coated potassium titanate whiskers.

[0039] Test Example 1: The high-strength aluminum alloy power cables prepared in Examples 1-3 and Comparative Examples 1-8 were tested as follows: Thermal conductivity: The thermal conductivity of the outer jacket layer was measured at 25°C using a Hot Disk thermal conductivity meter (TPS2500S) (W / m·K). Low temperature bending test: Bend the cable 180° around a cylinder 3 times its diameter at -20°C and observe whether the sheath cracks. Repeat the test 5 times. Tensile strength and elongation at break: tested in accordance with GB / T 1040.2-2022; Thermal aging test: After aging the cable sample at 100℃ for 168h, the tensile strength is tested and the tensile strength retention rate is calculated; The test results are shown in Table 1 below: Table 1

[0040] Combined with the aforementioned data, the thermal conductivity of Examples 1-3 is significantly superior to that of most comparative examples, demonstrating that the synergistic effect of the modified attapulgite, nano-hydrotalcite, and coated potassium titanate whiskers in the formulation effectively enhances heat dissipation. Due to the compatibilizing effect of the maleic anhydride graft copolymer and the uniform dispersion of the filler, the cables exhibit outstanding low-temperature toughness, achieving high levels of mechanical properties and thermal stability.

[0041] Comparative Example 1 lacks the interfacial compatibilizer of the maleic anhydride grafted copolymer, has poor filler dispersion, weak interface bonding, an increase in low-temperature cracking rate of 80%, a decrease in tensile strength of 20.7%, a decrease in elongation of 22.4%, and a decrease in thermal stability of 7.2%; Comparative Example 2 has unmodified attapulgite, low surface activity, weak bonding with the matrix, increased agglomeration tendency, a decrease in thermal conductivity of 13.5%, an increase in low-temperature cracking rate of 60%, and a decrease in tensile strength of 16.9%; Comparative Example 3 has no modified attapulgite, lacks a reinforcing skeleton, reduced mechanical strength and thermal conduction pathways, a decrease in thermal conductivity of 32.7%, complete cracking at low temperature, a decrease in tensile strength of 24.0%, and a decrease in thermal stability of 10.3%; Comparative Example 4 has no potassium titanate whiskers coated, has an unmodified surface, high interface thermal resistance, low stress transfer efficiency, a decrease in thermal conductivity of 11.5%, a 40% increase in low-temperature cracking rate, and a decrease in tensile strength of 14.0%; Comparative Example 5 lacks whisker reinforcement, and the reinforcement effect and thermal conduction path are reduced, resulting in a decrease in thermal conductivity. The number of nano-hydrotalcites decreased by 28.8%, the low-temperature cracking rate increased by 60%, and the tensile strength decreased by 19.4%; in comparative example 6, there was no nano-hydrotalcite, the barrier effect of the layer was lost, the thermal stability and thermal conductivity decreased, and the thermal conductivity coefficient decreased by about 38.5%. Nano-hydrotalcite, as a thermal conductive filler, is crucial to improving the heat dissipation performance of the cable sheath. The cracking rate in the low-temperature bending test deteriorated from 0 / 5 (no cracking) to 5 / 5 (all cracking). By enhancing the rigidity of the matrix and maintaining toughness, the low-temperature cracking resistance was significantly improved; after removal, the brittleness of the material increased sharply; in comparative example 7, the rubber phase was missing, the material became brittle, and the flexibility was lost. Although the tensile strength remained good, the elongation at break decreased by 43.3%, and it completely cracked at low temperature; in comparative example 8, there was no filler, the core reinforcement system was missing, the mechanical strength, thermal conductivity and thermal stability all decreased, the thermal conductivity decreased by 46.2%, it completely cracked at low temperature, the tensile strength decreased by 31.8%, the elongation decreased by 46.3%, and the thermal stability decreased by 15.5%.

[0042] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A high-strength aluminum alloy power cable, characterized in that: An aluminum alloy conductor layer and an outer sheath layer are sequentially arranged from the inside to the outside. The outer sheath layer comprises the following raw materials in parts by weight: 40-50 parts of low-density polyethylene, 20-30 parts of EPDM rubber, 8-15 parts of maleic anhydride grafted ethylene-vinyl acetate copolymer, 20-25 parts of modified attapulgite, 10-15 parts of nano-hydrotalcite, 6-8 parts of coated potassium titanate whiskers, 1.5-2 parts of dicumyl peroxide, 10-15 parts of magnesium hydroxide, 3-5 parts of zinc borate, 0.3-0.5 parts of antioxidant 1010, 0.2-0.4 parts of dilauryl thiodipropionate, 4-5 parts of calcium-zinc composite stabilizer, and 0.5-1 part of calcium stearate.

2. The high-strength aluminum alloy power cable according to claim 1, characterized in that: The preparation method of the modified attapulgite includes: immersing the attapulgite pretreated with alkali solution in a KH550 ethanol solution with a mass concentration of 4%-6%, a solid-liquid weight ratio of 1:9-1:11, ultrasonically treating the solution at 70±5°C and a power of 800-1000 W for 0.8-1.2 h, centrifuging the solution at 3000-4000 rpm for 10-15 min, and vacuum drying the solution at 80±5°C until the moisture content is ≤0.3%.

3. The high-strength aluminum alloy power cable according to claim 2, characterized in that: The alkali solution pretreatment step comprises: adding attapulgite to a 0.4-0.6 mol / L NaOH aqueous solution at a temperature of 55-65° C., with a solid-liquid weight ratio of 1:15-1:20, stirring at 200-300 rpm for 1.5-2.5 hours, centrifuging, and washing with deionized water until the filtrate has a pH of 7.0±0.

5.

4. The high-strength aluminum alloy power cable according to claim 1, characterized in that: The method for preparing the coated potassium titanate whiskers comprises: immersing the potassium titanate whiskers in a KH570 solution, stirring at 45-55°C and 100-150 rpm for 30-50 minutes, and drying with hot air at 80±5°C until the moisture content is ≤1.0%; placing the pretreated whiskers in a fluidized bed, spraying nano-SiO2 sol, and heat-treating at 120±5°C for 0.5-1 hour after coating to obtain the whiskers.

5. The high-strength aluminum alloy power cable according to claim 4, characterized in that: The potassium titanate whisker has a diameter of 0.2-0.5 μm and a length of 20-50 μm.

6. The high-strength aluminum alloy power cable according to claim 4, characterized in that: The weight ratio of KH570, water and ethanol in the KH570 solution is 2.5-3.5:75-85:5-15, and the weight ratio of potassium titanate whiskers to the KH570 solution is 1:12-1:

15.

7. The high-strength aluminum alloy power cable according to claim 4, characterized in that: The dosage ratio of the sprayed nano-SiO2 sol to the pretreated whiskers is 0.3-0.5 mL / g.

8. The high-strength aluminum alloy power cable according to claim 4, characterized in that: The conditions for spraying the nano-SiO2 sol are as follows: an inlet air temperature of 110-120°C, an atomization pressure of 0.15-0.25 MPa, and a spraying speed of 8-12 mL / min.

9. A method for preparing a high-strength aluminum alloy power cable according to any one of claims 1 to 8, characterized in that the steps include: Mix low-density polyethylene and EPDM rubber at a temperature of 155-165°C and a rotation speed of 40-50 rpm for 3-5 minutes; add maleic anhydride grafted ethylene-vinyl acetate copolymer, heat to 170-180°C, mix at 70-80 rpm for 5-6 minutes; add modified attapulgite and hydrotalcite in sequence, stir at 165-170°C and 50-60 rpm for 6-8 minutes. min, finally, potassium titanate whiskers, magnesium hydroxide, zinc borate, antioxidant 1010, dilauryl thiodipropionate, calcium zinc composite stabilizer, and calcium stearate are added and stirred at 140-150° C. and 30-40 rpm for 10-15 min; dicumyl peroxide is added, the speed is increased to 100-120 rpm, and vulcanization is carried out at 170-180° C. for 6-8 min. The cable is extruded and coated on the outside of the aluminum alloy conductor layer through a single-screw extruder, the temperature of the first zone of the extruder is 160-165° C., the temperature of the second zone is 165-170° C., the temperature of the third zone is 175-180° C., and the temperature of the die head is 180-185° C. After air cooling and irradiation cross-linking, the high-strength aluminum alloy power cable is obtained.

10. The method for preparing a high-strength aluminum alloy power cable according to claim 9, characterized in that: The energy of the irradiation cross-linking electrons is 1.5-2 MeV, and the irradiation dose is 15-20 kGy.